KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTS PADA MATERI HIMPUNAN - Amelia Rahmah Adhyan; Sutirna Sutirna (IKIP Siliwangi, 2022)
Students often answer the question given by the teacher in a trial manner, in which when answering the question of students not understanding the question first, on the reason that the problem given is different from the problem studied so that the student assumes that math lessons are hard to understand and make the head dizzy, because it causes the obtained results to be wrong. Therefore, the study aims to describe the potential mathematical solution of class VIII MTs students in assembly material at one of the schools in the khanebic district. The research method used is qualitative descriptive. The data analysis technique used was an interactive model of miles and hubermans. The subject used in the study is an eighth grader of 15 students taken under temptive sampling. The test instrument used is to describe the problem-solving and non-tes ability by conducting an interview. Results from the study indicate that the ability to solve a student's mathematical problem falls into three categories, with 26.7% of the student is high, 133% are moderate and 60% are low. The results suggest that students' capacity for mathematical problem solving is relatively low, which means there are several indicators of an optimum problem solving capability.